PROFILE OF CARE IN YOUNG WOMEN WITH BREAST CANCER IN AMAZONAS: 11 YEARS STUDY - Pereira, Hilka Flavia Barra do Espirito Santo Alves; Nunes, Gabriel Pacífico Seabra; Viapiana, Paulyne de Souza; Silva, Katia Luz Torres (Mastology, 2019)
A cross-sectional, retrospective cohort study was carried out to describe the profile of breast cancer patients aged 40 years or less diagnosed and treated at the CECON/FCECON Foundation from 2003 to 2013. The following were evaluated: age, staging, place of origin and diagnostic accuracy, through search of records in patients’ records. Data were computed in a database and analyzed through descriptive statistics. There were 211 patients under 40 years with breast cancer in the study period, representing 9.83%. The most affected age group was between 35 and 40 years. Regarding clinical staging, 57 cases were at stage IIA at diagnosis. About the method of screening, 71 patients performed it through clinical examination or self-examination and, in relation to the provenance, 48 cases were from other states. It is necessary to improve diagnosis in this age group and that the institutional care be directed to the patients of their original states.